2023
DOI: 10.3390/cancers15041294
|View full text |Cite
|
Sign up to set email alerts
|

Optical Genome Mapping as an Alternative to FISH-Based Cytogenetic Assessment in Chronic Lymphocytic Leukemia

Abstract: The fluorescence in situ hybridization (FISH) technique plays an important role in the risk stratification and clinical management of patients with chronic lymphocytic leukemia (CLL). For genome-wide analysis, FISH needs to be complemented with other cytogenetic methods, including karyotyping and/or chromosomal microarrays. However, this is often not feasible in a diagnostic setup. Optical genome mapping (OGM) is a novel technique for high-resolution genome-wide detection of structural variants (SVs), and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
0
12
0
4
Order By: Relevance
“…21 For in silico LLOD determination, the laboratory can use two samples, one with several abnormalities (preferably with different SV classes) and a normal control, and then down sample the molecule files (.bnx) in different proportions to represent the various "dilutions." 19 This process will demonstrate the limits of the assembly pipeline to detect low-level events. Please note that the LLOD is also dependent on variables such as quality of DNA (N50 >150 kb, map rate, coverage, CNA-tool/SV-tool), and coverage (see Section 3 for further detail).…”
Section: Limit Of Detectionmentioning
confidence: 97%
See 2 more Smart Citations
“…21 For in silico LLOD determination, the laboratory can use two samples, one with several abnormalities (preferably with different SV classes) and a normal control, and then down sample the molecule files (.bnx) in different proportions to represent the various "dilutions." 19 This process will demonstrate the limits of the assembly pipeline to detect low-level events. Please note that the LLOD is also dependent on variables such as quality of DNA (N50 >150 kb, map rate, coverage, CNA-tool/SV-tool), and coverage (see Section 3 for further detail).…”
Section: Limit Of Detectionmentioning
confidence: 97%
“…These include a general assessment of OGM in various hematologic malignancies [8][9][10][11] as well as focused evaluations in specific patient cohorts such as Acute Myeloid Leukemia (AML), 12 Pediatric AML, 13 Myelodysplastic Syndromes, 14 Acute Lymphoblastic Leukemia, [15][16][17] and Chronic Lymphocytic Leukemia. 18,19 These studies have all demonstrated that OGM has equal or better sensitivity and resolution for the detection of diagnostic and prognostic abnormalities in hematologic malignancies with relatively few discordances. As such, clinical laboratories are now pursuing OGM for detection of sentinel cytogenomic abnormalities in patients with hematological neoplasms.…”
Section: Concordance Studies Between Conventional Cytogenetics and Ogmmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversas publicaciones recientes han demostrado que el OGM es una buena alternativa como prueba de primera línea para la detección de alteraciones cromosómicas en diferentes neoplasias hematológicas 7,11,14 , principalmente en la leucemia mieloide aguda (LMA) 8,12 , los síndromes mielodisplásicos (SMD) 8,17 , la leucemia linfoblástica aguda (LLA) 5,6,10 y la leucemia linfática crónica (LLC) 9,13 (Tabla 3). No obstante, todavía no se han publicado guías internacionales que especifiquen cuándo sería recomendable priorizar esta tecnología frente a los métodos convencionales (cariotipo, FISH, microarrays genómicos) y en qué afecciones la aplicación del OGM supondría una mejora en el manejo de los pacientes.…”
Section: Situación Actual Del Mapeo óPtico Del Genoma En El Estudio D...unclassified
“…La tecnología de OGM ha sido probada con éxito en el análisis citogenómico de diferentes neoplasias hematológicas [5][6][7][8][9][10][11][12][13] . Numerosos estudios de validación han demostrado que, con una cobertura mínima de 400X, el OGM puede llegar a alcanzar una sensibilidad máxima cercana al 1%, una especificidad del 100% y un valor predictivo positivo superior al 80%.…”
Section: Introductionunclassified